Bcl-xL inhibits PINK1/Parkin-dependent mitophagy by preventing mitochondrial Parkin accumulation. (May 2020) - Yu, Si; Du, Mengyan; Yin, Ao; Mai, Zihao; Wang, Yong; Zhao, Mengxin; Wang, Xiaoping; Chen, Tongsheng
Highlights: Bcl-xL inhibits PINK1/Parkin-dependent mitophagy. Bcl-xL prevents mitochondrial Parkin accumulation. Bcl-xL physically interacts with Parkin in cytoplasm. Bcl-xL physically interacts with PINK1 on mitochondria. Abstract: This report aims to explore how Bcl-xL, a Bcl-2 family protein, regulates PINK1/Parkin-dependent mitophagy. Compared with the Hela cells expressing Parkin alone, co-expression of Bcl-xL significantly inhibited CCCP (Carbonyl cyanide 3- chlorophenylhydrazone)-induced mitochondrial Parkin accumulation and mitophagy. Western blotting analysis illustrated that over-expressed Bcl-xL inhibited CCCP-induced decrease of mitochondrial proteins in Parkin over-expressed cells. Fluorescence loss in photobleaching (FLIP) analyses demonstrated that Bcl-xL inhibited the CCCP-induced translocation of Parkin into mitochondria not by retrotranslocating Parkin from mitochondria to cytoplasm. Fluorescence resonance energy transfer (FRET) imaging revealed in Hela cells that Bcl-xL physically bound with Parkin to form oligomer in cytoplasm, and that Bcl-xL also directly interacted with PINK1 on mitochondria. analysis for HEK293 T cells verified that endogenous Bcl-xL interacted with both endogenous Parkin and PINK1. Collectively, Bcl-xL inhibits PINK1/Parkin- dependent mitophagy by preventing the accumulation of Parkin on mitochondria via two regulation ways: directly binds to Parkin in cytoplasm to prevent the translocation of Parkin from cytoplasm to mitochondria and directly binds to PINK1 on mitochondria to inhibit the Parkin from cytoplasm to mitochondria by PINK1.